A systematic review and meta-analysis revealing realistic outcomes following paediatric torsion of testes. Issue 6 (December 2018) - MacDonald, C.; Kronfli, R.; Carachi, R.; O'Toole, S.
Summary: Introduction: Reported testicular loss rates following paediatric testicular torsion often reflect the surgical decision-making process, rather than long-term survival of the testes. Objectives: We aim to perform systematic analysis and meta-analysis to investigate testicular salvage rates and to assess predictors of long-term viability. Study design: Systematic review according to PRISMA guidelines was performed to investigate immediate and long-term (>12 months) testicular loss rates following torsion in the paediatric population. Literature search and study inclusion were performed by two investigators. A study quality score was derived and attributed to each study. Predictors of testicular loss were described. Proportions meta-analysis was performed with random effects modelling, and testing for heterogeneity. Results: Twelve studies were includedm, 6 reporting early orchidectomy rates,  and 6 reporting long-term outcomes. Study quality was generally low. Discussion: The mean early testicular loss rate was 39%, whereas meta-analysis revealed late loss to approach 50%. Predictors of outcomes include prehospital symptom duration, location of presentation, transfer to a tertiary centre, social affluence and use of ultrasound prior to diagnosis or transfer. Conclusions: This study has shown a considerable late testicular loss rate, which must be relayed to families even after testicular salvage. Delay in time to presentation is consistently found to predict poor outcomes.